Solubility measurement, Hansen solubility parameters and solution thermodynamics of gemfibrozil in different pharmaceutically used solvents. (3rd August 2019) - Kalam, Mohd Abul; Alshehri, Sultan; Alshamsan, Aws; Alkholief, Musaed; Ali, Raisuddin; Shakeel, Faiyaz
Abstract: Gemfibrozil (GEM) is cholesterol-lowering agent which is being proposed as poorly water soluble drug (PWSD). Temperature based solubility values of GEM are not yet available in literature or any pharmacopoeia/monograph. Hence, the present studies were carried out to determine the solubility of PWSD GEM (as mole fraction) in various pharmaceutically used solvents such as water (H2 O), methanol (MeOH), ethanol (EtOH), isopropanol (IPA), 1-butanol (1-BuOH), 2-butanol (2-BuOH), ethylene glycol (EG), propylene glycol (PG), polyethylene glycol-400 (PEG-400), ethyl acetate (EA), dimethyl sulfoxide (DMSO) and Transcutol ® (THP) at the temperatures ranging from T  = 298.2 K–318.2 K under atmospheric pressure P  = 0.1 MPa. Equilibrium/experimental solubilities of GEM were recorded by applying a saturation shake flask methodology and regressed using 'van't Hoff and Apelblat models'. Hansen solubility parameters for GEM and various pharmaceutically used solvents were estimated using HSPiP software. The solid states of GEM (both in pure and equilibrated states) were studied by 'Differential Scanning Calorimetry' which confirmed no transformation of GEM after equilibrium. Experimental solubilities of GEM in mole fraction were observed maximum in THP (1.81 × 10 −1 ) followed by DMSO, PEG-400, EA, 1-BuOH, 2-BuOH, IPA, EtOH, PG, MeOH, EG and H2 O (3.24 × 10 −6 ) at T  = 318.2 K and similar tendencies were also recorded at T  = 298.2 K, T  = 303.2 K, T  = 308.2 K and T  = 313.2 K. 'Apparent thermodynamic analysis' on experimental solubilities furnished 'endothermic and entropy-driven dissolution' of GEM in each pharmaceutically used solvent.